The role of argumentation in language acquisition and the learning process of deaf children in bilingual schools - Silva, Ana Clara Jardim da (2024)
According to Leitão (2007a; 2007b), argumentation is a privileged mechanism for the acquisition of language and knowledge, covering dimensions such as dialogical-discursive, dialectical, social and epistemic. This demonstrates the importance of developing it in the first years of school, especially in bilingual schools. The objective of this study is, therefore, to analyze the argumentative speeches produced by deaf children, seeking to identify the enunciative-discursive chains that generate argumentation and the epistemic changes generated by the effect of these argumentative speeches. For this, data collection was carried out in three bilingual schools (Portuguese-Libras), focused on the education of the deaf, covering a sample of 23 subjects, between 6 and 14 years old, where naturalistic situations were observed and provoked by playful workshops. Drawing on studies in argumentation (LEITÃO, 2006, 2007a; VIEIRA, 2015), multimodality (SOUSA; MÁXIMO, 2009; CAVALCANTE, 2016; 2011) and dialogism (VOLÓCHINOV; BAKHTIN, 2018; BAKHTIN, 2016), it was possible to conclude that argumentation stimulates discursive and linguistic movements (such as resuming statements, reading the context and syntactic organization) and multimodal movements (facial expression, social gestures, use of the body, etc.) that corroborate bimodal bilingual acquisition. Thus, argumentation contributes to the deaf child's entry into the language and favors the interactional process, which is extremely important for the formation of critical thinking and the expected language development.